Genomics of high molecular weight plasmids isolated from an on-farm biopurification system - Martini, María Carla (2016)
The use of biopurification systems (BPS) constitutes an efficient strategy to eliminate pesticides from polluted wastewaters from farm activities. BPS environments contain a high microbial density and diversity facilitating the exchange of information among bacteria, mediated by mobile genetic elements (MGEs), which play a key role in bacterial adaptation and evolution in such environments. Here we sequenced and characterized high-molecular-weight plasmids from a bacterial collection of an on-farm BPS. The high-throughput-sequencing of the plasmid pool yielded a total of several Mb sequence information. Assembly of the sequence data resulted in six complete replicons. Using in silico analyses we identified plasmid replication genes whose encoding proteins represent 13 different Pfam families, as well as proteins involved in plasmid conjugation, indicating a large diversity of plasmid replicons and suggesting the occurrence of horizontal gene transfer (HGT) events within the habitat analyzed. In addition, genes conferring resistance to 10 classes of antimicrobial compounds and those encoding enzymes potentially involved in pesticide and aromatic hydrocarbon degradation were found. Global analysis of the plasmid pool suggest that the analyzed BPS represents a key environment for further studies addressing the dissemination of MGEs carrying catabolic genes and pathway assembly regarding degradation capabilities.